Active Layer Thermal Properties and Vegetation Recovery at a Site Experiencing Acid Drainage Near Eagle Plains, Yukon Territory, Canada - Comerford, Nicolas (Université d'Ottawa / University of Ottawa, 2023)
Acidic waters flowing over pyrite-rich shales are discharging near Eagle Plains, Yukon Territory, degrading the local vegetation and permafrost. Initial site investigations in 2005 found that high active layer soluble ion concentrations are likely preserving a supra-permafrost talik that recycles acidity from year to year. Using ground temperature measurements, we have determined that the loss of surface vegetation at the site has resulted in a 4°C to 6°C increase in ground surface and active later temperatures and a 1.7 to 5.1 times increase in active layer thermal diffusivity. Modeling has further shown that the change in energy balance at the ground surface accounts for the permafrost degradation at the site, and that the increased thickness of the active layer is sufficient to preserve the talik even under low salinity conditions. The thawing permafrost has however improved drainage and results in less surface runoff and improved groundwater flow that has disseminated acidity and contaminants throughout the active layer, leading to surface conditions that are more conducive to plant colonisation. Field investigations and analysis of satellite imagery demonstrate that this has reduced the surface expression of area affected by acid drainage by 53% from 2014 to 2021, and that successional changes in vegetation are occurring. Given long enough time periods, this may act as a negative feedback to permafrost degradation and allow the site to recover from past deterioration.
Keywords: acid drainage; permafrost; vegetation; talik